Impaired Antiviral Stress Granule and IFN-β Enhanceosome Formation Enhances Susceptibility to Influenza Infection in Chronic Obstructive Pulmonary Disease Epithelium - Hsu, Alan C.-Y.; Parsons, Kristy; Moheimani, Fatemeh; Knight, Darryl A.; Hansbro, Philip M.; Fujita, Takashi; Wark, Peter A. (American journal of respiratory cell and molecular biology, 2016)
Chronic obstructive pulmonary disease (COPD) is a serious lung disease that progressively worsens lung function. Those affected are highly susceptible to influenza virus infections that result in exacerbations with exaggerated symptoms with increased mortality. The mechanisms underpinning this increased susceptibility to infection in COPD are unclear. In this study, we show that primary bronchial epithelial cells (pBECs) from subjects with COPD have impaired induction of type I IFN (IFN-β) and lead to heightened viral replication after influenza viral infection. COPD pBECs have reduced protein levels of protein kinase (PK) R and decreased formation of PKR-mediated antiviral stress granules, which are critical in initiating type I IFN inductions. In addition, reduced protein expression of p300 resulted in decreased activation of IFN regulatory factor 3 and subsequent formation of IFN-β enhanceosome in COPD pBECs. The decreased p300 induction was the result of enhanced levels of microRNA (miR)-132. Ectopic expression of PKR or miR-132 antagomiR alone failed to restore IFN-β induction, whereas cotreatment increased antiviral stress granule formation, induction of p300, and IFN-β in COPD pBECs. This study reveals that decreased induction of both PKR and p300 proteins contribute to impaired induction of IFN-β in COPD pBECs upon influenza infection.